Effects of Game Addiction on Musculoskeletal System Discomfort and Mental Toughness in E-Sport Players - Kendal, Kübra; Ataç, Amine; Köse, İlkay Tuğçe (Addicta: The Turkish Journal on Addictions, 2021)
The aim of this study is to reveal the level of game addiction, musculoskeletal system complaints, and mental toughness and to investigate musculoskeletal system discomfort risk and mental toughness by the addiction level in e-sports players. The population of the study consisted of a total of 204 e-sports players on various platforms in Turkey, 94 of whom were game addicted and 110 were not according to the seven-item Game Addiction Scale. The players were given the Demographic Data Form, the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ), the Cornell Hand Discomfort Questionnaire (CHDQ), and the Sports Mental Toughness Questionnaire (SMTQ). In CMDQ and CHDQ parameters, neck (7.55 ± 18.16 vs. 2.06 ± 4.26; p = .014), upper back (9.32 ± 19.41 vs. 3.32 ± 7.56; p = .024), lower back (12.27 ± 24.93 vs. 2.75 ± 5.47; p = .007), hip (2.89 ± 9.90 vs. .88 ± 2.89; p = .013), right hand B (2.18 ± 10.34 vs. .24 ± 1.24; p = .005) and F regions (1.76 ± 3.81 vs. .82 ± 2.96; p = .041) were significantly better in the non-addicted group. In SMTQ, the control sub-dimension (10.68 ± 3.27 vs. 12.75 ± 2.67; p < .001) and total scores (36.32 ± 6.74 vs. 38.46 ± 7.11; p = .021) were significantly better in the non-addicted group. These findings reveal that as the game addiction score increases, the risk of musculoskeletal system discomfort increases and mental toughness decreases. These results should be taken into account in e-sports players where a sedentary lifestyle is at the forefront.